2018
DOI: 10.1111/jre.12620
|View full text |Cite
|
Sign up to set email alerts
|

Identification of genetic risk factors of aggressive periodontitis using genomewide association studies in association with those of chronic periodontitis

Abstract: To identify the genetic risk factors for aggressive periodontitis (AgP), it is important to understand the progression and pathogenesis of AgP. The purpose of this review was to summarize the genetic risk factors for AgP identified through a case‐control genomewide association study (GWAS) and replication study. The initial studies to identify novel AgP risk factors were potentially biased because they relied on previous studies. To overcome this kind of issue, an unbiased GWAS strategy was introduced to ident… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 66 publications
0
23
0
Order By: Relevance
“…It is of particular importance that other Sherlock ‐prioritized genes might be also essential for periodontitis, although some of the identified genes are not expressed in gingival tissues, but are almost exclusively expressed in leucocytes, for example SIGLEC5 , SIGLEC14 , and S100A12 . Previous studies identified SIGLEC5 (Munz et al, ; Shungin et al, ) as a genetic risk factor for both chronic periodontitis and aggressive periodontitis (Masumoto et al, ). Generally, the expression of SIGLEC5 is restricted to blood cells, spleen, and tonsils.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is of particular importance that other Sherlock ‐prioritized genes might be also essential for periodontitis, although some of the identified genes are not expressed in gingival tissues, but are almost exclusively expressed in leucocytes, for example SIGLEC5 , SIGLEC14 , and S100A12 . Previous studies identified SIGLEC5 (Munz et al, ; Shungin et al, ) as a genetic risk factor for both chronic periodontitis and aggressive periodontitis (Masumoto et al, ). Generally, the expression of SIGLEC5 is restricted to blood cells, spleen, and tonsils.…”
Section: Discussionmentioning
confidence: 99%
“…To identify the genetic risk variants for periodontitis, several genome‐wide association studies (GWAS) have been conducted worldwide (Hong, Shin, Ahn, Lee, & Kim, ; Masumoto et al, ; Munz et al, ; Offenbacher et al, ; Sanders et al, ; Teumer et al, ). For example, the GWAS by Munz et al identified nucleotide variants at SIGLEC5 and DEFA1A3 as risk loci for periodontitis (Munz et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Schaefer used genome-wide association studies to identify GLT6D1 as a risk gene factor for aggressive periodontitis (Schaefer et al, 2010). There have also been some other genome-wide association studies that have identified risk gene factors, such as DEFA1A3, SIGLEC5, and ANRIL (Masumoto et al, 2019;Vaithilingam et al, 2014). However, the genetic factors of aggressive periodontitis are not fully understood.…”
Section: Discussionmentioning
confidence: 99%
“…Candidate gene association studies were widely performed in previous periodontal research, focusing mainly on candidate genes related to immunity, inflammation, or bone metabolism that were thought to be associated with aggressive periodontitis. In contrast, a genome‐wide association methodology is capable of searching for candidate genetic risk factors on the genome‐wide scale, allowing the identification of genetic variants that are independent of inflammatory and immune genes and could not be detected in early candidate‐targeted studies (Masumoto et al, ; Munz et al, ; Vaithilingam et al, ). In the present study, we began to use NGS to detect the whole mitochondrial genome of patients with aggressive periodontitis on the basis of enlarged sample size.…”
Section: Discussionmentioning
confidence: 99%
“…Several factors have been linked to an increased incidence of periodontal disease and these can be divided into non-modifiable and modifiable factors (24). Examples of the former include aging, genetic predisposition, and osteoporosis, whereas the later include smoking, diabetes mellitus, psychological stress, alcohol consumption and poor oral hygiene (24)(25)(26)(27)(28)(29)(30)(31).…”
Section: Introductionmentioning
confidence: 99%